2001
DOI: 10.1002/ccd.1278
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherent reflectometry: A new technique to guide invasive procedures

Abstract: The success rate of percutaneous transluminal coronary angioplasty for chronic total arterial occlusions is still unsatisfactory. Inability to cross the lesion with a guidewire is a major cause of failure. Optical coherent reflectometry (OCR) is a new method of using laser light to measure the depth of tissue from the end of an optic fiber. This study tests whether an OCR prototype guidewire provides a guidance system that might be useful to assist reopening chronic total arterial occlusions. An OCR fiber opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
1
0
0
1
Order By: Relevance
“…The technology of optical coherence reflectometry provides the means to navigate the guidewire forward precisely, thereby minimizing the risk of perforation, and the capability of radiofrequency ablation increases the crossing potential of the wire. In vitro studies have confirmed that the system is able to differentiate plaque from the media/adventitia boundary accurately [14], and in vivo evaluation has shown efficacy of the ablation capacity even when used in heavily calcified vessels [5]. In the current study, failure of successful recanalization occurred in 48.3% lesions, related to dissection in six (42.9%).…”
Section: Discussionsupporting
confidence: 63%
“…The technology of optical coherence reflectometry provides the means to navigate the guidewire forward precisely, thereby minimizing the risk of perforation, and the capability of radiofrequency ablation increases the crossing potential of the wire. In vitro studies have confirmed that the system is able to differentiate plaque from the media/adventitia boundary accurately [14], and in vivo evaluation has shown efficacy of the ablation capacity even when used in heavily calcified vessels [5]. In the current study, failure of successful recanalization occurred in 48.3% lesions, related to dissection in six (42.9%).…”
Section: Discussionsupporting
confidence: 63%
“…Allerdings haben all diese neuen Geräte und Technologien (Frontrunner, SafeCross, Crosser etc. [14,15,17,33,35] Besonders wichtig bei dieser Vorgehensweise ist, darauf zu achten, den ersten Draht nicht zu weit paravasal am distalen Gefäß vorbeizuschieben, um dort das Auftreten eines intramuralen Hämatoms zu vermeiden. Dies würde zu einer Kompression des Lumens führen und damit zum Verlust der Kontrastfüllung des distalen Gefäßanschlusses und somit des Zielpunktes der Drahtmanipulation.…”
Section: Verbesserte Drahtrekanalisationstechnikunclassified